Discovery of pyrazolopyrrolidinones as potent, broad-spectrum inhibitors of Leishmania infection - Kavouris, John A.; McCall, Laura-Isobel; Giardini, Miriam A.; De Muylder, Geraldine; Thomas, Diane; Garcia-Pérez, Adolfo; Cantizani, Juan; Cotillo, Ignacio; Fiandor, Jose M.; McKerrow, James H.; De Oliveira, Camila I.; Siqueira-Neto, Jair L.; et al. (Frontiers in Tropical Diseases, 2023)
Leishmaniasis is a parasitic disease that affects more than 1 million people worldwide annually, predominantly in resource-limited settings. The challenge in compound development is to exhibit potent activity against the intracellular stage of the parasite (the stage present in the mammalian host) without harming the host monocytes. We identified a compound series (pyrazolopyrrolidinones) active against the intracellular parasites of Leishmania donovani and L. major; the causative agents of visceral and cutaneous leishmaniasis in the Old World, respectively. Members of the series showed high potency against the deadliest form, visceral leishmaniasis (approximate EC50 ≥ 0.01 µM without harming the host macrophage up to 10.0 µM). In comparison, the most efficient monotherapy treatment for visceral leishmaniasis is amphotericin B, which presents similar activity in the same assay (EC50 = 0.2 µM) while being cytotoxic to the host cell at 5.0 µM. Continued development of this compound series with the Discovery Partnership with Academia (DPAc) program at the GlaxoSmithKline Diseases of the Developing World (GSK DDW) laboratories found that the compounds passed all of GSK’s criteria to be defined as a potential lead drug series for leishmaniasis. Here, we describe preliminary structure-activity relationships for antileishmanial pyrazolopyrrolidinones, and our work to characterize the in vivo efficacy of select pyrazolopyrrolidinones in models of visceral and cutaneous leishmaniasis.